2019
DOI: 10.15326/jcopdf.6.1.2018.0134
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Patients with ZZ Versus SZ Alpha-1 Antitrypsin Deficiency: Findings from AlphaNet’s Disease Management Program

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…In national and international AATD registries, patients with the PI*SZ genotype generally constitute a smaller proportion of the total number of patients (from 1.0 to 21.3%), with the highest number of PI*SZ individuals reported by the Spanish registry (Table 1) [15][16][17][18][19][20][21][22][23][24][25]. However, not all of these individuals have symptomatic disease (index cases), as some registries, e.g., the Danish and Irish targeted detection programmes, conduct screening of family members of diagnosed individuals specifically to identify non-index cases [24,26].…”
Section: Prevalence Of the Pi*sz Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…In national and international AATD registries, patients with the PI*SZ genotype generally constitute a smaller proportion of the total number of patients (from 1.0 to 21.3%), with the highest number of PI*SZ individuals reported by the Spanish registry (Table 1) [15][16][17][18][19][20][21][22][23][24][25]. However, not all of these individuals have symptomatic disease (index cases), as some registries, e.g., the Danish and Irish targeted detection programmes, conduct screening of family members of diagnosed individuals specifically to identify non-index cases [24,26].…”
Section: Prevalence Of the Pi*sz Genotypementioning
confidence: 99%
“…Smoking is a key risk factor for the development of lung disease in patients with AATD and disease progression and survival are both significantly worse in smokers than never-smokers [4,42]. Recent studies have shown that identified PI*SZ individuals are more likely to have a history of tobacco smoking, and generally worse health than PI*ZZ individuals, and also demonstrate worse behaviours associated with poor health (such as lack of exercise) [16,17]. However, there are conflicting reports as to the individual impact of smoking on the development of lung disease in PI*SZ individuals.…”
Section: Influence Of Smokingmentioning
confidence: 99%
“…Whilst their milder genetic profile when compared with PiZZ makes PiSZ, SS, and MZ patients less likely to develop adverse effects linked to AATD, such genotypes are much more prevalent than ZZ in the world 5 7 , and in the presence of unhealthy behaviors they become big risk groups for the development of lung disease. This enhances public health need to increase diagnosis and implement preventive measures in these patients 7 , 8 .…”
Section: Which Patients Develop Clinically Relevant Disease?mentioning
confidence: 99%
“…The major clinical risk in PiSZ is the development of COPD, which is three times higher compared with PiMM 9 , less so in never-smoking patients 10 . When PiSZ patients develop emphysema, usually it has an apical dominance 5 ; physicians’ cognitive bias to screen for AATD mainly in basal emphysema may exclude them from testing and follow-up, thus leading to a greater proportion of undiagnosed patients relative to PiZZ. Reversibility has also been observed in a large number of patients, which is frequently associated with more severe airflow obstruction 10 .…”
Section: Which Patients Develop Clinically Relevant Disease?mentioning
confidence: 99%
“…In terms of genotype frequencies, two subjects were PiZZ and were already confirmed AATD cases. Another two subjects were identified as PiSZ and were also counted as severely deficient, though this may not be appropriate, since there is debate in the literature about whether the clinical risk attributable solely to the genetic mutation is similar [11,12]. In terms of heterozygosity of deficient alleles, 40 subjects carried a single Z and 143 a single S allele.…”
mentioning
confidence: 99%